1962
DOI: 10.1079/bjn19620059
|View full text |Cite
|
Sign up to set email alerts
|

A method of circulating and sampling the rumen contents of sheep fed on ground, pelleted foods

Abstract: 1962are described which were designed to test the effects of this method of circulating the rumen contents on the metabolism of food in the rumen and the efficiency with which the system mixed PEG with the rumen contents. E X PER I M E N T A LAnimals and their treatment. Three mature Greyface wethers of about IZO lb live weight were fitted, by the method of Ash (1957), with rumen cannulas of z in. internal diameter.T h e animals were given 500 g of pelleted diet at 7.30 a.m. and again at 7.30 p.m. The rations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The pump was based on an idea used by Sutherland et al (1962), but with an improved design and different materials. The basic principle was that of changing pressures in a large chamber at either ends of which were placed one way rubber 'flap' valves.…”
Section: Development Of the Rumen Juid Circulation Pumpmentioning
confidence: 99%
“…The pump was based on an idea used by Sutherland et al (1962), but with an improved design and different materials. The basic principle was that of changing pressures in a large chamber at either ends of which were placed one way rubber 'flap' valves.…”
Section: Development Of the Rumen Juid Circulation Pumpmentioning
confidence: 99%
“…In early studies, Gray et al (12) simply steam distilled rumen fluid to release all VFA and determined the concentration of radioactivity in the distillate after determining the total VFA present by titration. This method is still used by some workers (30). Weller et al (34) subsequently showed that the SR of a single labelled VFA could be used to give satisfactory estimate of the net flux of all three major VFA.…”
Section: Sample Analysismentioning
confidence: 99%